2020
DOI: 10.1007/s10272-020-0889-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Macroeconomic and Social Impact of the Coronavirus Pandemic in Latin America and the Developing World

Abstract: The COVID-19 pandemic will undoubtedly be a defi ning event in years to come both in economic, social and political terms. While the immediate impact of the coronavirus pandemic and the related economic slump was assessed to be of a similar magnitude to that of the Great Recession of 2007-2008 by mid-March 2020, the most recent fi gures of key variables such as the initial claims on unemployment insurance in the United States or the foreign new orders in Germany indicate that the current drop in economic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…Assim, esperava-se que os países mais ricos e com serviços de saúde pré pandemia melhor estruturados fossem capazes de coordenar com mais eficácia os atendimentos. Dessa maneira, evitariam o avanço da pandemia e reduziriam as taxas de mortalidade 19 . Por outro lado, presumia-se que países com sistemas de saúde fragilizados, com menor produto interno bruto (PIB) e, consequentemente, menor investimento em saúde, tivessem maior número de casos e óbitos pela COVID-19 19,20,21 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Assim, esperava-se que os países mais ricos e com serviços de saúde pré pandemia melhor estruturados fossem capazes de coordenar com mais eficácia os atendimentos. Dessa maneira, evitariam o avanço da pandemia e reduziriam as taxas de mortalidade 19 . Por outro lado, presumia-se que países com sistemas de saúde fragilizados, com menor produto interno bruto (PIB) e, consequentemente, menor investimento em saúde, tivessem maior número de casos e óbitos pela COVID-19 19,20,21 .…”
Section: Discussionunclassified
“…Dessa maneira, evitariam o avanço da pandemia e reduziriam as taxas de mortalidade 19 . Por outro lado, presumia-se que países com sistemas de saúde fragilizados, com menor produto interno bruto (PIB) e, consequentemente, menor investimento em saúde, tivessem maior número de casos e óbitos pela COVID-19 19,20,21 .…”
Section: Discussionunclassified
“…In Italy Conticini et al (28) discussed that important factors such as the age structure of the affected population, the great differences between the Italian regional health systems, the capacity of intensive care units in the region, and prevention policies adopted by the government have played a major role in the spread of and mortality for SARS-CoV-2, presumably more than long-term air pollution itself. The effect of poverty on COVID-19 mortality has been less described in the literature but it represents a major risk condition in developing countries probably related to unstable occupation and income, lower health literacy, and limited access to preventive health services (32, 33). A few recent ecological studies in the US at county level have reported a correlation between COVID-19 mortality rate and some social disparities such as poverty status and non-English speaking households and other ethnic minorities (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Since the World Health Organization (WHO) formally announced the SARS-CoV-2 as a global pandemic on March 11, 2020, there have been 110,224,709 confirmed cases of COVID-19, including 2,441,901 deaths on February 20, 2021. Without any doubts, COVID-19 pandemic has dramatic impact on numerous dimensions such as economic shock, logistics, supply chain, tourism industry, education, mental health, agriculture, food security, and animal sectors (Basilaia and Kvavadze 2020;Gagliano et al 2020;Grida et al 2020;McKibbin and Fernando 2020;Proaño 2020;Sahu 2020;Seleiman et al 2020;Williams 2021). Apart from the above-mentioned impacts, a work from home policy has been widely adopted as a part of government enforced quarantine measures to reduce the outbreak of pandemic (Purwanto et al 2020;Setyawan and Lestari 2020).…”
Section: Introductionmentioning
confidence: 99%